Probiotics Effect on Interleukin-4 (IL-4) and Imunoglobulin E (IgE) Levels on Asthmatic Patients - Pujiati, Pujiati (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: Probiotics may play a role in immune system maturation and may reduce the risk of allergies and asthma in childhood. However, the therapeutic benefits of probiotics in asthma depend on various factors such as strain of probiotics and dosing regimen. Objectives: The aims of this study was to evaluate the effect of probiotic (LactoB®) on Immunoglobulin E (IgE) and Interleukin (IL-4) serum level in childhood Asthma. Methods: Forty children aged 1-5 years with asthma were recruited into a randomized controlled trial. The children were assigned into a probiotic (Lactobacillus acidophilus, Bifidobacterium longun, Streptococcus; Lacto B®) or an equivalent volume of placebo, twice daily orally for 8 weeks. The IgE and IL-4 serum level were determined by ELISA. The differences between groups were analyzed by t-test dependent with confidence interval of 95%. Results: In intervention group, mean of IgE serum levels after the probiotics treatment was significantly lower compared to that of before the treatment (148.18 pg/mg; 283.20 pg/mg; respectively). Mean of IL-4 serum levels after the treatment was significantly lower compared with that of before the treatment (111.03 pg/mg; 142.08 pg/mg respectively). In control group, there were no significant differences between IgE serum levels mean before the administration of placebo and after the intervention (292.39 pg/ml; 286.94 pg/ml respectively). There were no significant differences between IL-4 serum levels mean before and after the treatment (136.76 pg/ml; 139.56 pg/ml).Conclusion: there was an effect of probiotics supplementation on IgE and IL-4 serum levels in childhood asthma.